Implementasi Pelayanan Digital Smart Branch pada Bank Mandiri Wahid Hasyim Kota Malang dalam Upaya Meningkatkan Kepuasan Nasabah - Niko Ariza Ramadhanu; Lingga Yuliana (Epsilon Journal of Management, 2025)
Digital Smart Branch as a form of banking digitalization is presented as the latest service strategy that makes it easier for people to enjoy banking services faster, easier and safer. The purpose of this study is to determine the implementation of Smart Branch digital services at Bank Mandiri Wahid Hasyim Malang in an effort to increase customer satisfaction. This study is a qualitative study with a method of collecting information through interviews with sources, books, literature reviews, literature, previous research, websites or articles that are relevant to the problem being studied. The results of the study indicate that with the Smart Branch service system, a strategy that can be applied to provide more efficient customer service is to utilize technology to personalize customer service, such as customized product recommendations or providing faster and easier problem solving.